Interactions of Interferons and SARS-CoV-2 Antibodies With Type 2 Diabetes - AL Hadeedy, Usama Emad; Karomi, Asma Sumiea (Iraqi Journal of Science, 2026)
Type 2 diabetes mellitus (T2DM), clinically depicted by insulin resistance and long-standing hyperglycemia, predisposes to infections and is further exacerbated in COVID-19 patients, thereby resulting in an increased risk of severe outcomes. The main objectives of this study were to evaluate type 2 diabetes and non-diabetic patients diagnosed with COVID-19 and compare them with control samples for levels of INF-α, INF-β, and SARS-CoV-2 antibodies (IgM/IgG). The study aims to determine the impact of type 2 diabetes on the immune response against SARS-CoV-2 and to understand which immunodeficiency could explain the poor prognosis in diabetic patients. A total number of 430 nasal swabs were collected from patients in Kirkuk between January 1, 2023, and June 7, 2023. The patients' ages ranged from (18 - 83) years, and through their polymerase chain reaction (PCR) tests, there were 72 confirmed cases of SARS-CoV-2, of which (51.4%) were males and (48.6%) were females and the majority were elderly. Type 2 diabetes patients were among the confirmed cases, with 43 patients and 29 non-diabetics. Blood samples were taken from these individuals and distributed into two tubes: one containing EDTA for testing glycated haemoglobin and the other containing gel for immunological studies using an ELISA device that measures the levels of IgG, IgM, INF-α, and INF-β. Immunological analysis showed that type 1 interferons were significantly less abundant in diabetic and non-diabetic patients compared to control samples. However, the antibody response, especially in terms of IgG and IgM levels, was significantly reduced in diabetic patients compared to non-diabetic individuals. This suggests that type 2 diabetes reduces the immune response in patients infected with SARS-CoV-2. This study suggests that type 2 diabetes is associated with reducing the immune cell response to SARS-CoV-2, as supported by lower levels of antibodies and type 1 interferons among the diabetic groups.